Water quality study in rambungan mangrove area - Noor' Ain, Jalim (Universiti Malaysia Sarawak, UNIMAS, 2008)
This study was conducted to determine the water quality status in Rambungan mangrove area and its associated tributaries. Three field samplings were carried out on 5 October and 10 December 2007 and 11 March 2008 at five different stations along Batang Rambungan. Physical and chemical water quality parameters namely salinity (ranged 11.67 ± 1.53 to 33.00 ± 0.00 ppt) , water temperature (26.90 ± 0.00 to 33.60 ± 1.15 °C), DO (4.00 ± 0.19 to 7.90 ± 0.10 mg/L), BOD5(0.60 ± 0.00 to 4.53 ± 0.01 mg/L), COD (39.00 to 153.00 mg/L), water transparency (0.37 ± 0.01 to 0.94 ± 0.01 m), pH (7.07 ± 0.06 to 8.12 ± 0.01), turbidity (7.84 ± 1.08 to 41.38 ± 11.39 FTU), TSS (10.33 mg/L to 84.66 mg/L), chlorophyll-a (0.47 μg/L to 2.69 μg/L), nitrate (0.04 mg/L to 0.43 mg/L), nitrite (0.009 mg/L to 0.058 mg/L), ammonia-nitrogen (1.56 mg/L to 4.31 mg/L), silicate (0.158 mg/L to 0.593 mg/L) and orthophosphate (0.06 mg/L to 0.42 mg/L) were measured and analyzed to determine the water quality status of Rambungan mangrove area. From the study, conclusion can be made that the water quality at Rambungan mangrove area was slightly polluted in terms of high concentration of nutrients due to the presence of human settlements and aquaculture activity.